Gender disparities in patients undergoing extracorporeal cardiopulmonary resuscitation - Springer, A.; Dreher, A.; Reimers, J.; Kaiser, L.; Bahlmann, E.; van der Schalk, H.; Wohlmuth, P.; Gessler, N.; Hassan, K.; Wietz, J.; Bein, B.; Spangenberg, T.; et al. (Frontiers in Cardiovascular Medicine, 2024)
The use of venoarterial extracorporeal membrane oxygenation (VA-ECMO) in extracorporeal cardiopulmonary resuscitation (eCPR) has emerged as a treatment option for selected patients in refractory cardiac arrest (CA). In the light of increasing availability, analys es of outcome-relevant predisposing characteristics are of growing importance. We evaluated the prognostic influence of gender in patients presenting with out of hospital cardiac arrest (OHCA) treated with eCPR.We retrospectively analysed data of 377 consecutive patients treated for OHCA using eCPR in our cardiac arrest center from 01/2016 to 12/2022. Primary outcome was defined as survival to hospital discharge with favourable neurological outcome (cerebral performance category[CPC]-score ≤2). Statistical analyses were performed using baseline comparison, survival analysis, as well as multivariable analyses.Results: Of the 377 studied patients, 69 (21%) were of female gender. Female patients showed less prevalence of pre-existing coronary artery disease (48% vs. 75%, p<0.001) and cardiomyopathy (17% vs. 34%, p=0.01) compared to the male patients, while mean age and prevalence of other cardiovascular risk factors were balanced. Primary reason for CA differed significantly (female: coronary event 45%, pulmonary embolism 23%, cardiogenic shock 17%; male: coronary event 70%, primary arrhythmia 10%, cardiogenic shock 10%; p=0.001). Prevalence of witnessed collapse (97% vs. 86%; p=0.016) and performance of bystander CPR (94% vs. 85%; p=0.065) was higher in female patients. Mean time from collapse to eCPR did not differ between the two groups (77±39 min vs. 80±37 min; p=0.61). Overall, female patients showed a higher percentage of neurologically favourable survival (23% vs. 12%; p=0.027) despite a higher prevalence of procedure associated bleeding complications (33% vs. 16%, p=0.002). Multivariable analysis identified a shorter total CPR duration (p=0.001) and performance of bystander CPR (p=0.03) to be associated with superior neurological outcome. Bivariate analysis showed relevant interactions between gender and body mass index (BMI).Our analysis suggests a significant survival benefit for female patients undergoing eCPR, possibly driven by a higher prevalence of witnessed collapse and bystander CPR. Interestingly, the